The relevance of the national entrepreneurship policy (Nep) 2030 in meeting the needs and strengthening the country’s entrepreneurial ecosystem: a snapshot - Irma Wani Othman; Saifulazry Mokhtar; Ismail Maidin; Mohd Maziz al-Hadi Moharam (Academic Inspired Network, 2021)
This paper established a snapshot on the relevance of the National Entrepreneurship Policy (NEP) 2030 in meeting the needs and strengthening the country’s entrepreneurial ecosystem. In this context, the focus is to identify various types of government development programmes in support of entrepreneurs, while creating a strong and competitive enterprise. Among the topics discussed were related to the significance of National Entrepreneurship Policy such as (a) cultural challenges and empower local entrepreneurs, (b) technology integration in entrepreneurship development, and (c) initiative for sustainable ecosystem. The direction of the discussion is on the country’s desire to realise superior entrepreneurship thus strengthening the entrepreneurial development ecosystem. In fact, the emphasis of government programme initiatives is focused on measuring results, intensifying collaboration across ministries, agencies and industries, enhancing the ability of entrepreneurs to be resilient, competitive and global in character and preparing entrepreneurs to be catalysts of trends and markets.